Detection of CFTR protein in human leukocytes by flow cytometry - Johansson, Jan; Vezzalini, Marzia; Verzè, Genny; Caldrer, Sara; Bolognin, Silvia; Buffelli, Mario; Bellisola, Giuseppe; Tridello, Gloria; Assael, Baroukh Maurice; Melotti, Paola; Sorio, Claudio (Cytometry. Part A, 2014)
Leukocytes have previously been shown to express detectable levels of the protein cystic fibrosis transmembrane conductance regulator (CFTR). This study aims to evaluate the application of flow cytometric (FC) analysis to detect CFTR expression, and changes thereof, in these cells. Aliquots (200 μL) of peripheral whole blood from 12 healthy control volunteers (CTRLs), 12 carriers of a CFTR mutation (CFC), and 40 patients with cystic fibrosis (CF) carrying various combinations of CFTR mutations were incubated with specific fluorescent probes recognizing CFTR protein expressed on the plasma membrane of leukocytes. FC was applied to analyze CFTR expression in monocytes, lymphocytes, and polymorphonuclear (PMN) cells. CFTR protein was detected in monocytes and lymphocytes, whereas inconclusive results were obtained from the analysis of PMN cells. Mean fluorescence intensity (MFI) ratio value and %CFTR‐positive cells above a selected threshold were the two parameters selected to quantify CFTR expression in cells. Lowest variability and the highest reproducibility were obtained when analyzing monocytes. ANOVA results indicated that both parameters were able to discriminate monocytes of healthy controls and CF individuals according to CFTR mutation classes with high accuracy. Significantly increased MFI ratio values were recorded in CFTR‐defective cells that were also able to improve CFTR function after ex vivo treatment with PTC124 (Ataluren), an investigative drug designed to permit the ribosome to read through nonsense CFTR mutations. The method described is minimally invasive and may be used in the monitoring of responses to drugs whose efficacy can depend on increased CFTR protein expression levels. © 2014 International Society for Advancement of Cytometry